Worldwide Occurrence of HIV-Associated Neurocognitive Disorders and Its Associated Factors: A Systematic Review and Meta-Analysis - Zenebe, Yosef; Necho, Mogesie; Yimam, Wondwosen; Akele, Baye (Frontiers in Psychiatry, 2022)
Background: HIV-associated neurocognitive disorders are common in people living with HIV/AIDS and affect the adherence of patients to prescriptions, activities of daily living, and quality of life of patients. However, there is a lack of summative evidence in the area. The present meta-analysis was therefore addressing this gap. Methods: We did our electronic search in Psych-Info, EMBASE, Scopus, and PubMed. The retrieved articles were stored with endnote reference manager and data was extracted using Meta-XL version 5.3. The quality of studies was evaluated with the modified Newcastle–Ottawa Scale (NOS). A random-effect model and STATA-16 were used to compute the average estimate of HAND. Heterogeneity was weighed with I2 statistics. A sensitivity analysis and subgroup analysis were employed. The existence /nonexistence of a publication bias were checked with the eggers test of publication bias. Results: The average prevalence of HAND was 50.41% (95% CI: 45.56, 55.26). The average estimate of HAND in Europe was found to be 50.015% whereas in Africa, Asia, and the United States of America (USA) it was 49.566%, 52.032 %, 50.407% respectively. The prevalence of HAND in studies that used the HIV Dementia Scale (IHDS) was 36.883% & 59.956% at cutoff points of IHDS< 9.5 & IHDS <10 respectively. Besides, the estimated average of HAND with the global dementia scale (GDS) was 40.766%. The prevalence of HAND in cross-sectional, cohort, and case-control studies was 49.52%, 54.087%, and 44.45% in that order. Socio-demographic variables; low level of education and older age, clinical and HIV related variables; the advanced stage of the illness and CD4 count of 500 cells/dl or less and psychological variables such as comorbidity of depression increases the risk of HAND. Conclusion: The prevalence of HIV-associated neurocognitive disorders was about 50.41%. Low level of education and older age, clinical and HIV related variables such as the advanced stage of the illness and CD4 count of 500 cells/dl or less, and comorbidity of depression were associated with HIV associated neurocognitive disorders. Public health interventions for HIV patients should target these essential problems.